Event‐Level Correlates of Drinking Events Characterized by Alcohol‐Induced Blackouts. (17th October 2019) - Merrill, Jennifer E.; Boyle, Holly K.; Jackson, Kristina M.; Carey, Kate B.
Abstract : Background: Prior research identifies a range of potential predictors of blackouts and suggests that blackouts increase risk for additional negative consequences. However, these studies are based on epidemiological work that allows us to draw conclusions about groups of people but not within‐person processes. The present study examined within‐person, event‐level correlates of blackouts. Methods: Ninety‐six heavy drinking college students (52% female) completed 28 days of daily reports of alcohol use and consequences, including blackouts. Thirty‐three participants reported 56 blackouts. Hierarchical linear modeling compared morning reports of drinking events on which participants did versus did not report a blackout, controlling for total drinks at the event. Results: Blackout likelihood increased as a function of total drinks consumed and of crossing thresholds for heavy episodic drinking (4+/5+ drinks for women/men) and high‐intensity drinking (8+/10+). Participants reported a higher total number of additional negative consequences on blackout events. Specific consequences that were more likely included embarrassing oneself and hangover. Blackouts were associated with morning ratings of less positive mood and a less favorable drinking event. Motives for drinking and simultaneous use of marijuana were not associated with blackouts. Conclusions: Event‐level findings of this study document that events leading to alcohol‐induced memory loss are associated with other adverse experiences relative to drinking events that do not result in blackout, and offer potentially motivational levers for preventive interventions. Abstract : Using a sample of 96 heavy drinking college students who completed 28 daily reports, we compared drinking events on which alcohol‐induced memory loss (i.e., blackout) was versus was not reported. Blackout likelihood increased with total drinks consumed, and participants reported more additional negative consequences on blackout events. Blackouts were associated with morning ratings of less positive mood and a less favorable drinking event. Providing these data to drinkers may motivate them to avoid drinking to the point of blackout.